An improved on-line measurement method of particulate matter concentration using tri-wavelength laser light scattering. (15th October 2021) - Han, Jinke; Liu, Xiaowei; Jiang, Meng; Wang, Zhaofeng; Xu, Minghou
Graphical abstract: Highlights: There is a power function correlation between average particle size and mass concentration sensitivity. The mass concentration sensitivity can be corrected by the ratio of scattered light at different wavelengths. The improved online measurement method significantly improves the accuracy of the mass concentration measurement. Abstract: Continuous monitoring of particulate matter (PM) from stationary source emissions is essential to reduce air pollution. The measurement accuracy of the widely used light scattering method is seriously affected by the particle characteristics, especially particle size. Based on the dependence of the scattered light on the particle size and incident wavelength, an improved on-line measurement method of PM mass concentration using tri-wavelength laser light scattering was proposed. Laboratory measurements on silica particles, Arizona dust, and fly ash from coal-fired power plants using this method were performed with a coupled laser. The experimental and theoretical results of silica particles showed an apparent power-law relationship between the PM mass concentration sensitivity (PMCS) and the average particle size. A linear function can approximate the relationship between the ratio of scattered light intensities at different wavelengths (RSDW) and the average particle size. The relationship between PMCS and RSDW established by particle size was introduced into the on-line correction of particle mass concentration measurement. The measurements of silica particles, Arizona dust, and fly ash obtained excellent correction effects. Compared with the uncorrected light scattering method, the average measurement deviations of mass concentration for three samples are reduced from 49.75% ± 1.11%, 48.62% ± 2.62% and 46.48% ± 0.83% to 8.11 ± 1.99%, 4.34 ± 2.26%, and 2.99 ± 0.55%, respectively.